Association of Obesity, Parity, and History of Knee Injury with Knee Osteoarthritis in Female - Ade Triyadi; Riardi Pramudiyo; Januarsih Iwan A. R. (Althea Medical Journal, 2015)
Background: Osteoarthritis is the most joint disorder among elderly. There are a lot of risk factors of knee osteoarthritis. Obesity and high frequent of parity can increase the load on knee joint. Knee injury also decreases the stability of knee joint on bearing body load. This study was conducted to observe the association of obesity, parity ≥3 times and history of knee injury with the occurrence of knee osteoarthritis in female aged >50 years old.